Evaluating ecosystem-based natural disaster management. Issue 7 (8th August 2020) - Ha, Kyoo-Man
Abstract: Not many rigorous researches have studied on how ecosystems have interacted with the occurrence of natural disaster. This article aims to evaluate the role of ecosystems in the field of natural disaster management with the ultimate goal of reducing its various impacts. Qualitative content analysis has been utilized as the principal methodology. Additionally, the ecosystem low-awareness approach has been compared with the ecosystem integration approach with respect to international institutions, national governments, business corporations, non-government organizations, and local communities. The most significant finding is that the field needs to transform its ecosystem low-awareness approach into the integration approach while addressing international networks, scientific research, holistic thinking, sustainability, and education. As a contribution, this article presents a more comprehensive evaluation of the issue of ecosystem regarding natural disaster management (as a common frame) than previous studies.